First report of mass mortality in hatchery-reared Sabah Pelian (Tor sp.) attributed to Aeromonas veronii in Sabah, Malaysia - Chin, Grace Joy Wei Lie; Kenneth Francis Rodrigues; Ching, Fui Fui; Helena Biun; Azhar Kassim; Rafidah Othman (Malaysian Society for Microbiology, 2024)
A breeding program for Sabah Pelian (Tor sp.) was initiated at the Universiti Malaysia Sabah (UMS) Hatchery Facility in July 2023. Fifteen Tor sp. were obtained from the Pagalan River, Tambunan, Sabah, and transported to the UMS Hatchery. After 12 days of acclimatization to the hatchery's conditions, followed by two days of heavy thundershowers, mass mortality was recorded on day 14. The goal of this study was to identify the cause of Pelian's mass mortality in the UMS Hatchery facility. The study involved the dissection of dead fish samples to assess internal organ conditions and the isolation of bacteria on microbial media. Despite normal water quality assessments, post-mortem examinations observed external skin lesions, haemorrhages and excessive mucus covering the body of the dead fish. Histopathological examination indicated a necrotizing inflammatory response in the ovarian tissue. Aeromonas veronii was isolated and identified as the causative agent through biochemical and molecular methods. Additionally, the antibiotic sensitivity test indicated varying degrees of susceptibility of A. veronii to the tested antibiotics. The bacterium showed resistance to ampicillin and erythromycin, while the remaining antibiotics exhibited sensitivity or an intermediate range of effectiveness. The two-day adverse weather prior to the mortality event was identified as the primary stress factor that likely induced the A. veronii infection, resulting in mass mortality of the Pelian. The study highlights the significance of understanding the interaction among fish, their internal microbiota and external environmental factors that may induce pathogenicity.